What's The Answer For 19 - (-29) = Topic: Math 1 Answer | Add Yours mjripalda | High School Teacher | (Level 1) Senior Educator Posted on September 6, 2013 at 12:14 AM `19-(-29)` First, simplify - (-29). To do so, apply the rule of multiplying numbers with like signs. So it becomes: `= 19 + 29` `=48` Hence, `19 - (-29)=48` . `19-(-29)` First, simplify - (-29). To do so, apply the rule of multiplying numbers with like signs. So it becomes: `= 19 + 29` `=48` Hence, `19 - (-29)=48` . We’ve answered 301,736 questions. We can answer yours, too. Ask a question

mjripalda | High School Teacher | (Level 1) Senior Educator Posted on September 6, 2013 at 12:14 AM `19-(-29)` First, simplify - (-29). To do so, apply the rule of multiplying numbers with like signs. So it becomes: `= 19 + 29` `=48` Hence, `19 - (-29)=48` . `19-(-29)` First, simplify - (-29). To do so, apply the rule of multiplying numbers with like signs. So it becomes: `= 19 + 29` `=48` Hence, `19 - (-29)=48` .